A Unified Trace Meta-Model for Alignment and Synchronization of BPMN and UML Models - Bouzidi, Aljia; Haddar, Nahla; Haddar, Kais (Informatica, 2025)
Organizations often face information system (IS) failures due to misalignment with business goals. Business process models (BPMs) play a crucial role in addressing this issue but are often developed independently of IS models (ISMs), resulting in non-interoperable systems. This paper proposes a traceability method to link BPMs and ISMs, bridging the gap between business and software domains. We introduce a unified trace meta-model integrating BPMN elements with UML constructs (use cases and class diagrams) via traceability links. This meta-model is instantiated as the BPMNTraceISM diagram, ensuring seamless integration through bidirectional transformation models. To validate our approach, we developed a graphical editor for BPMNTraceISM diagrams and implemented transformations using the ATLAS Transformation Language (ATL). A case study on a loan approval process demonstrates the method’s effectiveness in aligning BPMN and UML elements, improving interoperability and model alignment across domains.